Cells resistant to interferon are defective in activation of a promoter-binding factor. - Kessler, D S (1988)
Human cultured cell lines deficient in their ability to respond to type I interferon (IFN) fail to interrupt cellular proliferation or to induce an antiviral state following exposure to IFN alpha. Comparison of non-responsive Daudi and HeLa cell lines with IFN-responsive partner cell lines and examination of non-responsive Raji cells showed that the defective cell lines expressed type I IFN receptors of typical number and affinity and bound IFN equivalently compared to the normal cells. However, transcriptional induction of interferon-stimulated genes (ISGs) was greatly reduced and delayed in these cell lines, leading to reduced accumulation of ISG mRNA. Furthermore, the rapid activation of IFN-stimulated promoter binding factors whose appearance correlates with ISG transcriptional induction, did not occur in non-responsive cells. Thus, the primary defect of these cells leading to an impaired physiological response to IFN appears to be an inability to activate promoter-binding factors necessary to trigger ISG transcription, an obligate early step in antiviral and antiproliferative physiology.